Runnel development on granitic boulders on the foothills of Mount Kinabalu (Pinosuk Gravel Formation, Sabah, N Borneo) - Dodge-Wan, Dominique; Ramasamy, Nagarajan (2016)
Runnels are characteristic erosional features on karstified soluble rocks and can occasionally develop on less soluble rocks (i.e. sandstones and granites) but are poorly reported in Malaysia. This research summarizes boulder distribution, size, petrology and runnel morphology in a Pleistocene post-glacial mudflow on Mount Kinabalu. The goal is to investigate the runnel formation on granites. Colonization of boulders by cyanobacteria, mosses, lichens and higher plants is observed and related to rock surface meso-scale and micro-scale features. The coarse porphyritic texture of the granite contributes to the fragmentation and mechanical weathering of large K-feldspar crystals in the runnels. The damp runnel micro-environment is preferentially covered with mosses further enhancing weathering and erosion. As runnels deepen, the remnant protruding fins of rock weaken and may break off. The runnels are subaerial pseudokarst features, not the result of dissolution.